2022
DOI: 10.3390/d14010060
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Relationship between Richness and Morphological Diversity of Higher Taxa in the Darkling Beetles (Coleoptera: Tenebrionidae)

Abstract: Many studies have found that the correlation between species richness (SR) and morphological diversity (MD) is positive, but the correlation degree of these parameters is not always consistent due to differences in categories and various ecological factors in the living environment. Based on this, related studies have revealed the good performance of using higher taxa in biodiversity research, not only by shifting the testing group scale from local communities to worldwide datasets but also by adding different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…Recently, some insects have discovered the biodegradation of plastics at a high hourly rate. Yellow mealworms ( Tenebrio molitor Linnaeus 1758) and dark mealworms ( Tenebrio obscurus Fabricius 1792) are the insect larvae belonging to the family Tenebrionidae (or darkling beetles) in the seventh-most speciose taxon in order Coleopter, a which comprises of approximately 20,000 species across 2300 genera worldwide . The two species are observed around the world in grain storage as pest insects and are naturally present in forests with rotting wood where they eat dried leaves and lignocellulosic materials. ,, Both larvae are commercially reared as insect proteins and animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some insects have discovered the biodegradation of plastics at a high hourly rate. Yellow mealworms ( Tenebrio molitor Linnaeus 1758) and dark mealworms ( Tenebrio obscurus Fabricius 1792) are the insect larvae belonging to the family Tenebrionidae (or darkling beetles) in the seventh-most speciose taxon in order Coleopter, a which comprises of approximately 20,000 species across 2300 genera worldwide . The two species are observed around the world in grain storage as pest insects and are naturally present in forests with rotting wood where they eat dried leaves and lignocellulosic materials. ,, Both larvae are commercially reared as insect proteins and animal feed.…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses revealed that the pronotum width of both sexes is positively related to the use of insecticides. The internal muscles of the beetle pronotum is related to flight and movement [72,73], which enable them to adapt to different environmental conditions in diverse habitats [74]. Pronotum width has also been posited as a valuable trait in predicting population lifespan in some other beetle species [54].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the first catalog of Neotropical Coleoptera (Blackwelder 1944) included 286 species of darkling beetles recorded from Colombia, with no information about the distribution of the species within the country. Several phylogenetic studies (e.g., Doyen and Lawrence 1979, Kergoat et al 2014, Kanda 2017, Cheng et al 2022 have resulted in different nomenclatural arrangements, proposals, and revisions during the last decade (Bouchard et al 2005, Bremer and Martin 2014, Bousquet and Bouchard 2017, Bousquet et al 2018. In addition, scattered information on new species and new records has been published, reporting on material deposited in international collections (Marcuzzi 1954, Doyen 1989, Steiner Jr. 2004, Ferrer et al 2005, Aloquio and Lopes-A 2015; Smith and Sanchez 2015;Kanda 2016, Grey andSmith 2020), rendering Blackwelder's checklist out of date.…”
Section: Introductionmentioning
confidence: 99%